Cardiovascular disease related death among patients with esophagus cancer: A population-based competing risk analysis - Xia, Yang; Lin, Min; Huang, Jin; Fan, Li (Frontiers in Oncology, 2022)
Background: The proportion of non-cancer death in patients with esophagus cancer (EC) still increasing, especially cardiovascular disease (CVD) related death. The aim of this study was assess non-cancer causes of death and identified independent risk factors of CVD related death in EC patients. Method: Patients diagnosed with EC were extracted from the Surveillance, Epidemiology, and End Result database (SEER) database for analysis. Standardized mortality rates (SMRs) for non-EC deaths were calculated, the risk of death were assessed and compared with US general population. Multivariate competitive risk analysis were performed to select independent risk factors for death from CVD in EC patients. Results: A total of 43739 EC patients were enrolled and 35139 died during follow-up, of which 4248 died from non-cancer cause of death. The risk of non-cancer death in EC patients was 2.27-fold higher than in the general population (SMR=2.27). CVD were the most important cause of non-cancer death in EC patients, accounting for 43.4% of non-cancer of deaths. Compare with the general population, EC patients have higher risk of death from disease of heart (SMR, 2.24; 95% CI, 2.13-2.35), pneumonia and influenza (SMR, 2.92; 95% CI, 2.50-3.39), septicemia (SMR, 5.01; 95% CI, 4.30-5.79), along with other causes. Advanced age, male sex, well differentiated and moderately differentiated, localized stage, unmarried state, diagnosed between 2000-2009, receive radiotherapy were independent risk factor for CVD related death in EC patients. Conclusion: Non-cancer cause of death has become an important cause of death in EC patients. Improving public awareness of the major risk factors for non-cancer death is beneficial to the prevention and treatment of malignant tumors.